THE ILLUSION OF TRANSPARENCY: A CRITICAL ANALYSIS OF GOOD VILLAGE GOVERNANCE IN MANAGING CORPORATE SOCIAL RESPONSIBILITY (CSR) PROGRAMS - In Naka Malik Hardiansyah; Tituk Diah Widajantie (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
This study aims to analyze the application of good governance principles by the Semambung village government in managing the Corporate Social Responsibility (CSR) program from local businesses. This study uses a qualitative method with a case study approach, involving fourteen informants from various stakeholders, including business entities, village government, and village community. Data collection techniques include interviews, documentation, and field observations. Data analysis uses source triangulation and methodological triangulation to validate the data. Data were analyzed with the help of Nvivo 15 software. The research results show that the Semambung village government has not yet implemented good governance, as it is still lacking in transparency in budget management and is unresponsive to criticism and suggestions from the community. The accountability demonstrated by the Semambung village government is limited to the completion of Corporate Social Responsibility (CSR) program events, without conducting evaluations for the subsequent period. The application of legitimacy theory and stakeholder principles has not been implemented well. The Semambung village government must fully utilize the knowledge possessed by each of its village officials to receive a good evaluation from its community. The contribution of this research will assist the Semambung village government and other village governments in creating a good internal control system so that the management carried out can run as optimally as possible